Learning Disabilities, Types, Causes And Symptoms: A Case Study Of East Jerusalem Governorate Schools. - Edkadek, Husun (International Humanities Studies, 2026)
This study addressed the notion of learning disabilities (LD), its types, causes and symptoms at East Jerusalem Governorate Schools. This study shed the light on the educational challenges facing East Jerusalem, under the on-going Israeli occupation since the 1967, and the deliberate neglect of education and schools by the occupation in particular, as part of specific policies aimed at erasing Palestinian education and identity. Findings showed that learning disabilities (LD) are lifelong, neurological disorders that interfere with basic learning skills like reading, writing, and math, affecting how a person processes information. They are not reflections of intelligence but rather unexpected gaps between potential and performance, often caused by genetic, developmental, or brain-based factors. Finds showed that Dyslexia, Dysgraphia, and Dyscalculia are the most are the common types of learning disabilities. The study call for an early diagnosis for learning disabilities that involves comprehensive evaluations by specialists (e.g., psychologists, educators) rather than a single test.